2006
DOI: 10.1892/0891-6640(2006)20[1376:mdiccp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma-Related Disorders in Cats Commonly Present as Extramedullary Neoplasms in Contrast to Myeloma in Human Patients: 24 Cases with Clinical Follow-up

Abstract: Background: Myeloma-related disorders (MRD) are rare neoplasms of plasma cells. Published case reports describe a diversity of clinical presentations with confusing terminology and diagnostic criteria as a consequence of the assumption that MRD in cats are analogous to those in dogs or humans. Objective: The aim of the study was to describe clinical, clinicopathologic and imaging findings, response to treatment, survival and possible associations with other diseases or vaccination in a large case series. A pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 24 publications
7
40
1
Order By: Relevance
“…24 However, in a recent review of 24 myeloma-related disorders in cats, over 40% of cats with noncutaneous extramedullary plasmacytomas (internal organ involvement) had bone marrow infiltration by neoplastic plasma cells. 25 In contrast, we are aware of only 1 report of a cat with cutaneous extramedullary plasmacytoma progressing to multiple myeloma. 26 The incidence of solitary osseous plasmacytomas progressing to multiple myeloma in cats is unclear.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…24 However, in a recent review of 24 myeloma-related disorders in cats, over 40% of cats with noncutaneous extramedullary plasmacytomas (internal organ involvement) had bone marrow infiltration by neoplastic plasma cells. 25 In contrast, we are aware of only 1 report of a cat with cutaneous extramedullary plasmacytoma progressing to multiple myeloma. 26 The incidence of solitary osseous plasmacytomas progressing to multiple myeloma in cats is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…1,23,25,27 In the study reporting 8%, not all cats had complete skeletal surveys so it is possible osteolytic lesions were missed and the incidence was actually higher. 25 At the other end of the spectrum was a retrospective study indicating 67% of the cats with multiple myeloma had osteolytic bone lesions. However, the study was performed at an orthopedic referral center with the potential for case selection bias toward cats with clinical signs associated with osteolysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 A recent retrospective study found that unlike in human and canine myeloma cases, cats commonly have extramedullary involvement at initial presentation while radiographically detectable bone lesions are absent. 10 Regarding cell morphology, plasma cell tumors are fairly constant and most of them are found in the skin with the digestive tract being the second most common location. 11 Intraocular occurrence of noncutaneous extramedullary plasmacytomas is extremely rare and most human cases have been described in association with multiple myeloma, 12 while only one case involving the uveal tract has been described in the cat, however, without an associated amyloid.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, MM and advanced extramedullary plasmacytoma cannot always be distinguished by these criteria; therefore, the diagnostic criteria for MM in cats remain controversial. 3e5 Recently, Mellor et al proposed an all-encompassing term 'myeloma-related disorders (MRD)' for neoplasms of plasma cell origin in cats, and indicated that cats with MRD commonly had extramedullary involvement at the initial clinical presentation 6 while human patients with the MM did not. 7,8 In the present report, we describe a feline case of MRD showing a progressive increase in the number of atypical plasma cells in the peripheral blood.…”
mentioning
confidence: 99%